Relative consumption preferences and public provision of private goods - Tobias König; Tobias Lausen (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
This paper shows that the public provision of private goods may be justified on pure efficiency grounds in an environment where individuals have relative consumption concerns. By providing private goods, governments directly intervene in the consumption structure, and thereby have an instrument to correct for the excessive consumption of positional goods. We identify sufficient conditions when the public provision of private goods is always Pareto-improving, even when (linear) consumption taxes are available. In fact, with the public provision of private goods, there are cases where first-best allocations can be achieved, and a luxury tax on the positional good is redundant.
Keywords: H42; D62; D63; 330; public provision; social preferences; status-seeking